Student Perception and Experience of AI-Based Application: A Study On The Use Of ChatGPT In English Writing Learning - Fitriani, Desy; Rachman, Dzul (Universitas Syiah Kuala, 2025)
This study examines students' perceptions and experiences in using ChatGPT, an artificial intelligence-based application, in learning English writing. Using mixed methods, data was obtained through questionnaires involving 40 students and interviews involving 3 students from the English Education program in 1st semester at Universitas Muhammadiyah Kalimantan Timur (UMKT). The findings indicated that while ChatGPT is perceived as accessible and easy to use, a significant number of students expressed neutrality or concerns regarding its efficacy in supporting English writing development. However, many students were uncertain about its contribution to improve their writing skills, with some expressing doubt about the accuracy of its suggestions and concerns about over-reliance on the tool. This study concluded that despite its potential, ChatGPT's effectiveness in enhancing English writing remained debatable due to these reservations.